Labor Policy Analysis for Jobs Expansion and Development - Aniceto Jr. C. Orbeta; Vicente B. Paqueo; Leonardo Jr. A. Lanzona; Dean Gerard C. Dulay (Philippine Institute for Development Studies (PIDS), 2014)
The Philippines is at a crossroad. It can choose to continue to follow current unrealistic policies that despite good intentions have been shown to be actually detrimental to the poor. Or, it can elect to try another development path to get a better chance at reducing poverty.This study proposes a 12-point agenda, conveniently referred to as the Jobs Expansion and Development Initiative (JEDI) for poverty reduction. JEDI has two objectives. One is to expand gainful jobs through the acceleration of labor intensive production, particularly, the manufacturing of tradable commodities. The other is to improve investments in education and other human capital development and sustain total factor productivity gains. These objectives require inter alia minimum wage reform, which should be undertaken immediately, while investors are looking for new places to locate labor-intensive production and the Philippine economy is getting another look as a potential destination.The study recognizes the Filipinos' aspirations for secure jobs with decent wages. But it challenges the idea that imposing minimum wages and other current labor regulations should be the weapons of choice. They do not work; worse, there is preponderant evidence of its detrimental consequences. Alternatives should, therefore, be considered, such as better education, increased labor-intensive manufacturing, and greater opportunities for training on the job. Arguably, alternatives like these might take time. Consequently, bridging social protection programs need to be implemented in the meantime to help the poor directly with their subsistence needs. For this, instead of imposing mandatory minimum wages, the paper points out that it would be better to use direct and temporary income subsidy, carefully targeted to extremely poor households to meet suitable norms that society considers a public good. Such an approach would be both efficient and equitable, conforming to the general principle of public economics that a public good should be financed by general tax revenues.The study concludes that the time has come for the country to leave the beaten path and try new approaches that would rebalance current labor laws and practices to expand gainful jobs and minimize unintended consequences detrimental to the poor, the young, the women, the less educated, and the unorganized workers.
Keywords: J24; J31; J32; J38; 330; Philippines; jobs; minimum wages; labor market policy; human resource policy